Peran Badan Usaha Milik Desa(BUMDes) Dalam Meningkatkan Perekonomian Masyarakat di Desa Batu Belanak Kecamatan Suak Midai Kabupate Natuna - Nur Izzati; Afrizal Afrizal; Eki Darmawan (Populer: Jurnal Penelitian Mahasiswa, 2024)
Village-Owned Enterprises are institutions that operate in the field of managing village economic resources which aim to optimize village assets, improve community businesses and increase village income. This increasingly narrow agricultural area has caused the people of Batu Belanak Village to complain because some of their harvests have failed, such as coconuts, the quality of the coconut harvest is not good so it is not suitable for sale and consumption by the local community. This research method uses qualitative research. The data collection technique is using interviews and documentation. There are 4 indicators according to Siagian's role theory (2000:142-150), namely Stabilizer, Innovator, Pioneer and Modernizer. The results of this research show that the role as a stabilizer for the sale of electricity tokens and telephone credit, cattle fattening is one of the BUMDes programs that is running in Batu Belanak Village, the need for cattle, especially Midai Island, the price of sacrificial cattle is too high and the cows that come out will get big profits, fishing gear for Village BUMDes fishermen Batu Belanak provides credit for goods. BUMDes provides credit for goods in installments. The role of BUMDes innovator in Batu Belanak Village will be to create a household credit program. The government's role as a pioneer is to first implement innovation to build cooperation with the community in terms of advancing the village. Role as a modernizer from traditional to modern conditions.